Dynamic mechanical properties and wave propagation of composite rock-mortar specimens based on SHPB tests - Zhenyu Han; Diyuan Li; Xibing Li (International Journal of Mining Science and Technology, 2022)
Filled inclusions in rock discontinuities play a key role in the mechanical characteristics of the rock and thereby influence the stability of rock engineering. In this study, a series of impact tests were performed using a split Hopkinson pressure bar system with high-speed photography to investigate the effect of interlayer strength on the wave propagation and fracturing process in composite rock-mortar specimens. The results indicate that the transmission coefficient, nominal dynamic strength, interlayer closure, and specific normal stiffness generally increase linearly with increasing interlayer stiffness. The cement mortar layer can serve as a buffer during the deformation of composite specimens. The digital images show that tensile cracks are typically initiated at the rock-mortar interface, propagate along the loading direction, and eventually result in a tensile failure regardless of the interlayer properties. However, when a relatively weaker layer is sandwiched between the rock matrix, an increasing amount of cement mortar is violently ejected and slight slabbing occurs near the rock-mortar interface.